Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

The questions are in the image attached as a file. Please answer step by step. Thanks a lot.

The questions are in the image attached as a file. Please answer step by step. Thanks a lot.
 

Question Image
Grade:12

1 Answers

Antara
45 Points
15 days ago
51.f(r,n)=n-n^2{nn(1+1/n)(1+1/rn)(1+1/r2n).......}n.        (Taking n common from each bracket)
         = n-n^2 . nn^2 {1+1/n)(1+1/rn).....}n
 Taking log both sides,
ln(f(r,n))=n{ln(1+1/n)+ln(1+1/rn)+ln(1+1/r2n)+......}
 
Taking lim n->inf both sides
RHS=lim(n->inf) {nln(1+1/n)+nln(1+1/rn)+nln(1+1/r2n)+.......}
 
Now lim(n->inf) n *ln(1+1/n)   (inf*0 form of limit)
                        = lim(n->inf)  \frac{ln(1+1/n))}{1/n}
                       =lim(n->inf)    \frac{1/(1+1/n)*(-1/n^2)}{-1/n^2}…............(L hospital rule)
                      = 1
similarly second term=1/r , 3rd term=1/r^2 and so on
so ques 51. ans =e(1+1/r+1/r^2+1/r^3+.......inf)=e3/2  (Putting r=3 and applying sum of inf GP formula)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free